(untitled) - Devedzic, Vladan (New York, 2006)
The first section of Semantic Web and Education surveys the basic aspects and features of the Semantic Web. After this basic review, the book turns its focus to its primary topic of how Semantic Web developments can be used to build attractive and more successful education applications. The book analytically discusses the technical areas of architecture, metadata, learning objects, software engineering trends, and more. Integrated with these technical topics are the examinations of learning-oriented topics such as learner modeling, collaborative learning, learning management, learning communities, ontological engineering of web-based learning, and related topics. The result is a thorough and highly useful presentation on the confluence of the technical aspects of the Semantic Web and the field of Education or the art of teaching. The book will be of considerable interest to researchers and students in the fields Information Systems, Computer Science, and Education
Keywords: Semantic Web,Internet in education,Web ngữ cảnh